Securing India's Future In The New Millennium - Brahma Chellaney Ed; CHELLANEY (Brahma) Ed (Hyderabad: Orient Longman, 1999)
The first comprehensive study of the different facets of India s national security, the book looks ahead at the challenges of the coming years. India s leading experts on strategic affairs, including seven advisers to the National Security Council examine the tasks that lie ahead. This book is designed to initiate a wider public debate on those challenges and opportunities and help India develop a strategic culture and an institutionalised, integrated approach to national security.
Keywords: Military Science; Lessons of History; Technology and Energy; Non Military Instruments; Military Power